15 Biventricular assessment and quantification of primary mitral regurgitation is feasible and reproducible during continous supine exercise cardiovascular magnetic resonance. (4th June 2021) - Craven, Thomas; Jex, Nicholas; Gorecka, Miroslawa; Higgins, David; Brown, Louise; Das, Arka; Chowdhary, Amrit; Thirunavukarasu, Sharmaine; Sharrack, Noor; Dall'Armellina, Erica; Levelt, Eylem; Swoboda, Peter; et al.
Abstract : Background: Biventricular volume and great vessel flow assessment during continuous supine free-breathing exercise cardiovascular magnetic resonance (Ex-CMR) has recently been validated in healthy volunteers using Compressed SENSEx3 (CS3) sequences. Exercise transthoracic echocardiography (TTE) provides prognostic information in primary mitral regurgitation (MR). Resting CMR offers reference standard biventricular assessment and MR quantification with superior reproducibility to TTE. Ex-CMR assessment of biventricular volumes and quantitated MR may offer additional prognostic information in primary MR. Therefore we aimed to determine the feasibility of biventricular assessment and MR quantification in primary MR patients during continuous supine Ex-CMR using CS3 sequences. Methods: 10 asymptomatic patients with at least moderate primary MR on TTE (8 male, median age 62, 55-67years interquartile range) underwent continuous in-scanner (1.5T Philips Ingenia) supine cycle ergometer (Lode BV) Ex-CMR. Target heart rates (THR) were individually prescribed using heart rate reserve (HRR) and age predicted maximal heart rate model. Participants exercised for 2-minutes at no resistance, then an increase of 25-Watts every 2-minutes until THR achieved at low (30-39% HRR), then moderate (40-59% HRR) exercise. CMR imaging: free-breathing CS3 respiratory navigated short axis cine imaging and free-breathing CS3 aortic phase-contrast magnetic-resonance at rest, low and moderate exercise stages. MR was quantified indirectly from LV and aortic stroke volumes. Intra/inter-observer reproducibility was assessed by coefficient of variance (CV). Results: All patients completed the Ex-CMR protocol without complication. During exercise, there were no statistically significant changes in biventricular volumes or global left ventricular ejection fraction (LVEF) ( table 1 ). From rest to low and moderate exercise: right ventricular ejection fraction increased (55±5.4% to 60±6.0% and 63±6.6% respectively, p=0.001) and MR fraction decreased (40±14% to 36±11% and 30±15% respectively, p=0.006). Intra-observer reproducibility ( table 2 ) was excellent (CV <10%) except MR fraction & volumes during moderate and right ventricular end-systolic volumes (RVESV) during both exercise stages, which were good (CV10-20%). Inter-observer reproducibility ( table 2 ) was excellent (CV<10%), except RVESV and MR volumes at all stages, left ventricular end-systolic volumes during low and MR fraction during moderate exercise, which were good (CV 10-20%). Conclusion: Biventricular assessment and MR quantification during continuous supine Ex-CMR is feasible and reproducible in asymptomatic primary MR patients. Research assessing the techniques prognostic ability in primary MR patients is now warranted. Conflict of Interest: Nil